The Determinant of Credit Decisions in PT. Polatama Kusuma Madiun Financing - Dian Dian; Citaningtyas Citaningtyas; Ari Kadi (Economics and Digital Business Review, 2020)
This study aims to determine and provide empirical evidence between interest rates, service quality, and corporate image on the decision to take credit at PT. Polatama Kusuma Madiun Financing The sample was taken using purposive sampling technique, that is, the sample was taken based on criteria, with a total of 96 respondents from Polatama Kusuma People's Credit Bank. The data analysis used is multiple linear regression. The results of this study indicate that interest rates, service quality, and corporate image have a significant positive effect on the decision to take credit at the Polatama Kusuma People's Credit Bank. The results show the value of the standardization coefficient or service quality variable compared to the standardization coefficient or interest rate and company image. This means that the service quality variable has a dominant influence on the decision to take credit at PT. Polatama Kusuma Madiun Financing.